1,4-Disubstituted-1,2,3-triazole Linked Cyclic Ketones as Cytotoxic Agents - Karki, Subhas S.; Metikurki, Basavaraj; Das, Arnika; Madarakhandi, Ashok; Kumar, Arnav; Kumar, Sujeet; Schols, Dominique (Asian Journal of Chemistry, 2025)
A series of 1,2,3-triazole-linked cyclic ketones (AR 1-14) were synthesized involving the condensation of triazole-aldehydes with cyclic ketones in tetrahydrofuran and potassium hydroxide. The synthesized derivatives were evaluated for their in vitro cytotoxicity against retinal (hTERT RPE-1)-1), pancreatic (Capan-1), myeloid (K-562, Hap-1), colorectal (HCT 116), lung (NCI-H460), lymphoblastic (DND-41) and non-Hodgkin lymphoma (Z-138) cells. Among the tested derivatives, compound 2,6-bis(4-((1-(4-fluorobenzyl)-1H-1,2,3-triazol-4-yl)-methoxy)benzylidene)cyclohexanone (AR-7) exhibited moderate cytotoxic property with an IC50 of 11.8 µM and 13.6 µM against pancreatic adenocarcinoma and colorectal carcinoma cells, respectively. Molecular docking against galectin-1 receptor (PDB ID: 4Y24) demonstrated a favourable binding interaction (-7.1 kcal/mol) indicating a strong receptor-ligand affinity.